Skellig - Almond, David, 1951- (London : Hodder, 1998)
Michael, whose family is preoccupied with his ill baby sister, embarks on a new friendship with a girl named Mina and encounters a mysterious creature named Skellig--who may be a man, bird, or angel.
Keywords: Angels -- Fiction; Family life -- England -- Fiction; Moving, Household -- Fiction; Strangers -- Fiction; Angels -- Fiction; Family life -- England -- Fiction; Large print books; Moving -- Fiction; Strangers -- Fiction; England -- Fiction; England -- Fiction